Trends in portuguese adolescents’ sexual behavior from 2002 to 2014 : HBSC portuguese study - Reis, Marta (2019)
© 2018 The Author(s). Published by S. Karger AG, Basel on behalf of NOVA National School of Public Health. This article is licensed under the Creative Commons AttributionNonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND) (http://www.karger.com/Services/OpenAccessLicense). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.